LEAST-COST RATIGNS FOR BROILERS - A LINEAR PROGRAMMING APFROACH (1979)
It has been established that Nigeria has a food problem especially where protein intake is concerned. The poultry industry has been identified as the quickest means of expanding protein supply and lowering its cost within the short run (10-12 weeks for broilers). However, feeds account for 65-75 percent of the total costs of production. Moreover, the numerous problems facing the feed industry coupled with the poor quality of feeds produced have greatly limited the profitability and rapid expansion of the industry. The linear programming (L.P.) tool was utilized to formulate least-cost diets which made use of locally available ingredients. The scarcity and rising costs of the grains (maize and guinea-corn) which provide over 60 percent by weight of broiler feeds prompted the use of cassava flour as an energy providing Substitute. Feeding trials were carried out to test the efficiency of the least-cost diets. The objectives of the study are (1) To use L. P tool to formulate different least-cost rations which meet specific nutritional specifications for broilers, using readily available feed ingredients. Cassava and soya-bean are being tested as energy and protein providing substitutes respectively. (2) To compare the least-cost formulated diets with the diets used by some commercial farms. (3) To find the optimum killing age/weight. (4) To find the rate of Substitution of cassava flour for maize and guinea-corn in the ration for broilers. (5) To determine the economics of using different levels of cassava flour in the rations for broilers. Experimental results showed that starter diets with 24 percent Protein and 5 percent fibre level were better than those with 26 percent protein and 3 percent fib re levels. The computerised starter and finisher diets tested were cheaper and were found to perform better than the commercial diets. For the cassava based diets, analysis of the experimental results showed significant (P < 0.01, P < 0.05, differences in Feed Conversion Efficiency (F.C.E.) in both starter and finisher diets in which guinea- corn and maize were replaced. For weight gain, significant (P 0.01) differences were found only in Starter and finisher diets in which cassava replaced maize. For feed intake, significant differences (P < 0.0l) occurred only in Starter diets in which cassava replaced maize. The diets that caused significant differences were those in which the cassava contents were very high (25-40 percent) and they performed poorest. Even though growth is suppressed due to reduced feed intake caused by the powdery nature of the feeds, it is pertinent to note that diets with 40 percent cassava are still highly tolerable to the birds. Analysis of the weight response as cassava level increases showed that the decrease in weight gain was more rapid when cassava was being substituted for by maize rather than by guinea-corn. This could be attributed to the availability of nutrients or the amino-acid balance of the guinea-corn based diets. Carcass qualities of the birds were not taken into consideration because they are not highly rated in this society. The diets were further investigated to see how the nutrients contents and energy-based ingredients influenced performance, using the multiple linear regression model. The square root and quadratic functions were fitted but the quadratic forms gave the lead equations using the laid down criteria. Feed, protein, energy and the amino-acids intakes proved to be significant explanatory variables for the live- weight gain in the birds. Marginal Analysis was performed on some selected functions. The elasticity of production for energy and protein showed increasing returns to scale in the Starter and finisher diets at the mean value of inputs. As higher levels of inputs are used, diminishing returns is likely to set in. The elasticity of Substitution exhibits a unitary one also at the mean value of inputs. A percentage increase in the energy content of the feed results in an equal percentage decrease in the protein level of the diet. The extent of substitution is limited by the requirement of the birds. Optimum quantities of the energy-based ingredients to produce the Optimum broiler weight gain were determined. Production surfaces, isoquants and isoclines were produced for selected functions of the energy-based ingredients. The rate of Substitution between guinea-com/cassava and maize/cassava were found to be declining with increasing level of output as more of cassava and less of maize or guinea-corn are used. Estimates of revenue over feed costs for the various diets were computed. It was discovered that non-significant differences between diet without cassava was not synonymous with equal revenue yielding diets. In general, the computerised diets without cassava gave higher revenue than the commercial diets. For the diets in which cassava replaced the grains, the revenue accruing to the farmer decreased as the percentage cassava content increased. The revenue from guinea-corn diets were however higher than in the maize diets. Diets with 10 percent cassava had higher or equal revenue with the commercial diets. Diets with higher cassava levels were costlier because cassava is costlier than the grains. It is however envisaged that prices of cassava may fall in the near future because of increases in production. Revenue from the diets was therefore obtained using varying costs of diets as cassava price varies. When cassava was made to assume the same price with guinea-corn, all the computarised diets except that with 30 percent cassava level had higher revenues than the commercial diets. The revenue increased as the cassava prices were reduced but the diets with 30 percent cassava gave the lowest revenue all the time. Optimum killing age determined suggested that broilers be sold at eleven weeks for most of the diets except those in which five and 10 percent cassava replaced guinea-corn. The implications of this study are that efforts to improve returns — poultry farmers must be focused on the cost and quality of feeds. Particular attention must be paid to cheap sources of protein, carbohydrate and oils. There is a very high potential for the use of cassava if its adoption becomes a reality in the future. Further investigations are necessary in testing the least-cost diets with the existing various breeds of broilers. Comparison can also be made of the use of soya-bean and groundnut cake as a protein providing ingredient in broiler diets.